IMPROVING STUDENTS’ ACTIVENESS IN SPEAKING USING JIGSAW II OF SMAN 1 KENDAWANGAN - Azizah, Muna Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research was aimed to improve students’ activeness in speaking using Jigsaw II to class XI IPA 1 of SMAN 1 Kendawangan in academic 2016/2017. In this research, the researcher implemented Jigsaw II as the technique. The actions were designed in order to improve students’ activeness in speaking by discussing and presenting the material. The subject of this research were the students from class XI IPA 1 of SMAN 1 Kendawangan in academic year 2016/2017. The method of this research was a classroom action research. The researcher observed the improvement of students’ activeness in speaking by collecting the data through observation and measurement technique. The data were in the form of observation checklist, and field notes. The data were collected by analyzing field notes and observation guidelines during the research and by measuring the students’ mean score. This research was done in three cycles. The result of this research showed that Jigsaw II was effective to improve students’ activeness in speaking. The students’ mean score improved from 2.1 in the first cycle, 3 in the second cycle to 3.3 in the third cycle. It can be concluded that students’ activeness in speaking taught by Jigsaw II was improved. In other words, this technique can help the students to speak actively. Keywords: Jigsaw II, Activeness in Speaking, Classroom Action Research Abstrak Penelitian ini bertujuan untuk meningkatkan keaktifan siswa dalam berbicara menggunakan Jigsaw II pada kelas XI IPA 1 SMAN 1 Kendawangan tahun ajaran 2016/2017. Dalam penelitian ini, peneliti mengimplementasikan Jigsaw II sebagai teknik mengajar. Penerapan dibuat dengan tujuan untuk meningkatkan keaktifan berbicara siswa melalui diskusi dan presentasi. Subyek dari penelitian ini adalah siswa kelas XI IPA 1 SMAN 1 Kendawangan tahun ajaran 2016/201. Metode yang digunakan adalah penelitian tindakan kelas. Peneliti menyelidiki peningkatan keaktifan berbicara siswa dengan mengumpulkan data dari observasi dan catatan lapangan. Data diolah dengan menganalisis hasil observasi dan catatan lapangan selama penelitian dan menghitung nilai rata-rata siswa. Penilitian ini selesai dalam tiga siklus. Hasil menunjukkan bahwa Jigsaw II efektif untuk meningkatkan kemampuan berbicara siswa. Nilai rata-rata siswa meningkat dari 2,1 pada siklus pertama, 3 pada siklus kedua, 3,3 pada siklus ketiga. Dapat disimpulkan bahwa keaktifan berbicara siswa diajar menggunakan Jigsaw siswa meningkat. Dengan kata lain, teknik ini dapat membantu siswa berbicara dengan aktif. Kata Kunci: Jigsaw II, Keaktifan Berbicara, Penelitian Tindakan Kelas